PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK RASIO KEUANGAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Natasya Emanuella Dwi Jayanti; Sugiarto Prajitno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence regarding the effect managerial ownership, institutional ownership, firm size, leverage, profitability, sales growth, frequency of audit committee meetings, and independent commissioner towards earnings management. The company used in this research is a manufacturing company listed on the the Indonesia Stock Exchange (IDX) from 2017 until 2020. The number of samples that were obtained using the method were 67 companies dan a total of 196 data. This study uses multiple regression methods to examine the effect of the independent variables on the dependent variable. The result of this study indicate that sales growth has an effect on earnings management. While, managerial ownership, institutional ownership, firm size, leverage, profitability, frequency of audit committee meetings, and independent commissioner have no effect on earnings management.